2012
DOI: 10.1039/c2cc33847e
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature reversible C–H activation mediated by a Pt(0) center, and stoichiometric biphenyl formation via solvent activation

Abstract: Room temperature reversible C-H activation mediated by a designed diphosphine platinum complex is presented. These findings are demonstrated through mechanistic studies involving kinetics, isotopic effects, and corroborated by DFT calculations. The coupling between two unactivated aromatic derivatives is also demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The Pt–P (2.315(3) Å) and Pt–Cl (2.310(3) Å) bond lengths measured for 3a are comparable to the Pt–P bond length of 2.337(2) Å and Pt–Cl bond length of 2.317(2) Å of the complex trans -Pt(PCy 3 ) 2 Cl 2 . The Pt–P bonds for the cis -aldol complex 3b are significantly shorter at 2.258(3) Å, while the Pt–Cl bond lengths are longer at 2.367(2) Å and correlate well with the measured bond lengths of the complex Pt(PCy 2 CH 2 CH 2 CH 2 PCy 2 )Cl 2 . The differences in bond lengths are due to the high trans influence of phosphine ligands.…”
Section: Resultssupporting
confidence: 51%
“…The Pt–P (2.315(3) Å) and Pt–Cl (2.310(3) Å) bond lengths measured for 3a are comparable to the Pt–P bond length of 2.337(2) Å and Pt–Cl bond length of 2.317(2) Å of the complex trans -Pt(PCy 3 ) 2 Cl 2 . The Pt–P bonds for the cis -aldol complex 3b are significantly shorter at 2.258(3) Å, while the Pt–Cl bond lengths are longer at 2.367(2) Å and correlate well with the measured bond lengths of the complex Pt(PCy 2 CH 2 CH 2 CH 2 PCy 2 )Cl 2 . The differences in bond lengths are due to the high trans influence of phosphine ligands.…”
Section: Resultssupporting
confidence: 51%
“…Noting predictions that the ability of (PP)­Pt(0) to effect C–H oxidative addition should depend on the P–Pt–P bite angle, with medium values expected to be favorable, the authors generated the six-membered ring species 17 and found that, on reduction to Pt(0), benzene or toluene added reversibly to give a reasonably stable Pt­(II) aryl hydride, which rather surprisingly reacted further (slowly at room temperature, faster at 80 °C) to biaryls and dimeric Pt hydride 18 (Scheme ). DFT calculations suggest that the latter step proceeds via a second oxidative addition of arene to give a Pt­(IV) intermediate, (PP)­PtH 2 Ar 2 , followed by C–C reductive elimination . More recent calculations on methane activation by a variety of d 10 LM and L 2 M centers (where M is a group 9, 10, or 11 metal), including L 2 Pt­(0), suggest that it is bite angle flexibility, rather than the actual bite angle value itself, that governs reactivity …”
Section: C–h Activation At Ptmentioning
confidence: 99%
“…DFT calculations suggest that the latter step proceeds via a second oxidative addition of arene to give a Pt(IV) intermediate, (PP)PtH 2 Ar 2 , followed by C−C reductive elimination. 51 More recent calculations on methane activation by a variety of d 10 LM and L 2 M centers (where M is a group 9, 10, or 11 metal), including L 2 Pt(0), suggest that it is bite angle flexibility, rather than the actual bite angle value itself, that governs reactivity. 52 A rare example of a stable Pt(II) alkyl hydride, anionic complex 19, was prepared by the stepwise route of Scheme 19, not by C−H activation; DFT calculations predict that oxidative addition of C−H bonds to (as yet hypothetical) [(PCN)Pt] − should be kinetically and thermodynamically favorable.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…For terminal alkynes, the coordination and the oxidative addition competed, giving a mixture of the (η 2 -alkyne)­Pt 0 and the hydrido­(alkynyl)­Pt II products that did not show interconversion upon continued heating. Reversible C–H activation of aromatic compounds has also been observed for these (bisphosphine)­Pt 0 fragments. , Although NHCs have proven to be an outstanding class of ancillary ligands, the application of (NHC)­Pt 0 complexes in the cleavage of C–H bonds has remained relatively unexplored, as has been reverse reactions involving C–H reductive elimination from Pt­(II). Nevertheless, Pt(0) complexes have been found to activate the C–H bonds of imidazolium rings to yield (NHC)­Pt II hydride compounds .…”
mentioning
confidence: 99%